Paperless reality: transnational parenthood and undocumented Nepalese in Portugal - Budal, Aashima (2018)
Undocumented working migrants are economic agents who produce wealth in the country where they reside, paying taxes, but not having legal rights. This happens with a substantial number of the Nepalese residing in Portugal. Furthermore, the large majority of them is qualified, in terms of school education, although not able to progress professionally due to their irregular situation. This study focuses on the contemporary immigration of Nepalese undocumented in Portugal and its impacts on families. The aim was to understand how transnational parenting is being practiced and perceived by Nepalese mothers and fathers living in Portugal, in an irregular situation. This study employed a qualitative method through microethnography, by using in-depth interviews and participant observation. Among eight participants of the research, six were Nepalese challenged by distance and an undocumented situation, with families who stayed in Nepal; and two were key informants having solid information on them. The findings, firstly, evidence the perilous migration trajectories of the Nepalese, as well as their frustrated expectations, mobility descendant and exploitation as irregular migrants. Because the macro level policies and borders are becoming stricter, there is space for migrant smugglers to charge for Nepalese migrants who wish to work in Portugal. Secondly, the outputs revealed gender differences concerning mothers and fathers parenting at distance, while undocumented, as well as their coping mechanisms. Thirdly, the results demonstrate that the Nepalese are living undocumented, while being qualified and working in precarious jobs and high debts to the intermediaries. This study further contributes for the reflection on social worker’s implications in giving support to irregular migrants.